2017
DOI: 10.3949/ccjm.84.s1.03
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of exercise in the management of type 2 diabetes

Abstract: Exercise is typically one of the first management strategies advised for patients newly diagnosed with type 2 diabetes. Together with diet and behavior modification, exercise is an essential component of all diabetes and obesity prevention and lifestyle intervention programs. Exercise training, whether aerobic or resistance training or a combination, facilitates improved glucose regulation. High-intensity interval training is also effective and has the added benefit of being very time-efficient. While the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
196
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(220 citation statements)
references
References 56 publications
11
196
0
13
Order By: Relevance
“…Physical activity has been shown to benefit several metabolic disorders, including obesity, diabetes and fatty liver disease (Kirwan et al, 2017). Older cross-sectional studies suggested exercise might prevent age-related bone loss (Krolner et al, 1983; Prince et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has been shown to benefit several metabolic disorders, including obesity, diabetes and fatty liver disease (Kirwan et al, 2017). Older cross-sectional studies suggested exercise might prevent age-related bone loss (Krolner et al, 1983; Prince et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, these interventions lack a resistance training component, and this is particularly important where weight loss is accompanied by a loss of lean tissue (Baba et al, 1999;Brehm et al, 2005;Saris et al, 2000;Solomon et al, 2010). Increasing recognition of the role of lean mass in the regulation of blood glucose in T2D (Kirwan, Sacks, & Nieuwoudt, 2017;Srikanthan & Karlamangla, 2011) has prompted the American Diabetes Association to add 2-3 days of resistance training per week to their physical activity recommendations (Colberg et al, 2016). Nonetheless, while the addition of resistance exercise training to physical activity recommendations is a welcome step, the added exercise burden is unlikely to increase adherence to exercise recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent investigation conducted in T2DM patients compared the effect of AET, lasting at least 30 min per day from 3 to 7 days a week, with RT [127]. It was observed that RT improved muscle strength by 10%-15% and exerted beneficial effects on lipid profile, blood pressure, bone mineral density, insulin sensitivity, and muscle mass [128,129].…”
Section: Exercise Training For the Management Of Diabetes Mellitus: Cmentioning
confidence: 99%